Light weight meshes in incisional hernia repair - Schumpelick Volker (Journal of Minimal Access Surgery, 2006)
Incisional hernias remain one of the most common surgical complications with a long-term incidence of 10-20%. Increasing evidence of impaired wound healing in these patients supports routine use of an open prefascial, retromuscular mesh repair. Basic pathophysiologic principles dictate that for a successful long-term outcome and prevention of recurrence, a wide overlap underneath healthy tissue is required. Particularly in the neighborhood of osseous structures, only retromuscular placement allows sufficient subduction of the mesh by healthy tissue of at least 5 cm in all directions. Preparation must take into account the special anatomic features of the abdominal wall, especially in the area of the Linea alba and Linea semilunaris. Polypropylene is the material widely used for open mesh repair. New developments have led to low-weight, large-pore polypropylene prostheses, which are adjusted to the physiological requirements of the abdominal wall and permit proper tissue integration. These meshes provide the possibility of forming a scar net instead of a stiff scar plate and therefore help to avoid former known mesh complications.